(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Less clear, fast and accurate information about the inventory of goods often occurs in every company, as well as what happens in the inventory system of PT Estetika Pro International. Recording business processes are still done manually, there are no warnings for inventories reaching the minimum limit, difficulties in determining inventory for the next month/period, and data duplication is the cause of unclear, slow and inaccurate inventory information. The purpose of this research is to produce an inventory application that can manage inventory data so that data duplication and accumulation of goods do not occur. Moreover, it can reduce delays in inventory information that is useful for decision making in meeting customer needs. The development methodology used is the waterfall method. The tools used are UML (Unified Modeling Language), using PHP programming language and MySql database. The final result of this research is to produce a database system that can manage company data and minimize errors in handling goods and produce inventory applications that have sales, purchases, returns, shipping, history of goods, thinning goods warnings and reports of goods with a user-friendly and computerized display.